AN ANALYSIS OF THE IMPLEMENTATION OF LEARNING AND INNOVATION SKILLS IN 21ST CENTURY EDUCATION IN TEACHING ENGLISH AS FOREIGN LANGUAGE IN SMA NEGERI 2 SINGARAJA - Prayoga, H.; Padmadewi, N. N.; Agustini, D. A. E. (Jurnal Pendidikan Bahasa Inggris undiksha, 2020)
The 21st century education brings changes in the classroom practices that are increasingly complex along with the development of the technology. This demands the teachers to adapt their teaching and insert 21stcentury skills in the classroom. This research aimed data analyzing how EnglishÂ  teachers implements learning and innovation skills of 21st century education in teaching English as a foreign language in SMA Negeri 2 Singaraja. A mixed-method was implemented as the method in this study. The research subjects were4 English teachers in SMA Negeri 2 Singaraja. Due to pandemic situation of Corona virus, the data were collected using questionnaire and interview without observations. The results of the questionnaire and interview showed that English teacher inserted learning and innovation skills in their objectives and activities in lesson plans and the English teacher taught the students by inserting the learning and innovation skills. However, the teachers faced problems especially in choosing appropriate materials for their students who are in different levels of abilities.Keyword: 21st century skills, learning and innovation skills